Preparation and characterization of organoclays synthesized from Thanh Hoa bentonite and demethyl dioctadecyl ammonium chloride - Cam, Nguyen Thi Dieu; Noi, Nguyen Van; Lan, Duong Thi Ngoc; Hang, Nguyen Thu; Phong, Dao Thanh (Vietnam Journal of Chemistry, 2012)
In this study, organoclays were synthesized by placing dimethyl dioctadecyl ammonium (DMDODA) cation onto bentonites. The structure of modified bentonites was studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), chemical analysis, thermal analysis and FT-IR spectra. The intercalation of the DMDODA cation increased the interlamellar distances from 15.6Å (Na-bentonites) to 40.57Å. The effect of temperature, pH, time and amount of quaternary ammonium salt on the distance layer of organoclays was addressed.